Implementasi Nilai Shiddiq dan Amanah dalam Praktik Jual Beli oleh Pedagang Disabilitas (Studi Kasus UMKM Universitas Islam Negeri Raden Mas Said Surakarta) - Febian Candra Dinata; Nadya Anatasya; Lulu Nur Erliani; Ardila Dwi Candra Winata; Moch. Rifki Abdullah; Renata Luhtitisari; Waluyo Waluyo (Al Barakat, 2026)
This study aims to analyze the implementation of the values of shiddiq (honesty) and amanah (trustworthiness) in buying and selling practices among traders with disabilities at the MSMEs of State Islamic University of Raden Mas Said Surakarta. This research is motivated by the importance of applying Islamic business ethics in economic activities, especially for entrepreneurs with disabilities who, despite their physical limitations, are still able to run their businesses independently and professionally. The research subjects consisted of traders with physical disabilities and visual impairments who actively operate businesses within the campus MSME environment. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving traders with disabilities and related parties. Data analysis was conducted using the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the value of shiddiq is reflected in the traders’ honesty in conveying the condition, quality, and prices of products to consumers without any manipulation of information. Meanwhile, the value of amanah is demonstrated through the traders’ responsibility in maintaining product quality, providing timely services, and consistently fulfilling customer orders. Traders with disabilities also build customer trust through friendly communication, consistent service, word-of-mouth promotion, and the use of social media as a marketing tool. The implementation of the values of shiddiq and amanah contributes to increasing consumer trust and supporting the sustainability of MSMEs within an Islamic-based campus environment.